Astrocyte: An Innovative Approach for Alzheimer's Disease Therapy - Bronzuoli, Maria R.; Facchinetti, Roberta; Steardo, Luca; Scuderi, Caterina (Current Pharmaceutical Design, 2017)
Alzheimer's disease (AD) is a devastating neurological illness with a heavy economic impact. Further comorbidities in combination with the social impact of this disorder increase the urgency of a clearer comprehension of its etiopathogenesis, allowing the execution of novel therapeutic strategies. Despite astrocytes have been widely described as active participant in the regulation of cerebral circuits, available data are still poor. Even less information is available about their precise role in the pathogenesis of illness. Moreover, the scant knowledge about the astrocyte-neuron interplay in health and disease still impedes pioneering discoveries. The focus of this review is to look for new and innovative pharmacological approaches against AD. In order to perform this, we used the following keywords in PubMed search engine: astrocytes, therapy, Alzheimer's disease, and glia in different combinations. With this review, we collected data available in literature describing how also astrocytes besides neurons might be new potential targets for drug discovery. Different approaches currently being studied include modulation of glutamate transporters expression, astroglial genetic manipulation, free radicals inhibition, up-regulation of neurotrophins, and regulation of astrogliosis and neuroinflammation. Since several studies already demonstrated that astrocytes are definitely involved in AD pathogenesis, these cells can represent a promising new therapeutic target.
Keywords: reactive gliosis